2023
DOI: 10.1519/jsc.0000000000004556
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Intrasession Exercise Order of Flywheel Resistance and High-Intensity Interval Training on Maximal Strength and Power Performance in Elite Team-Sport Athletes

Abstract: Petré, H, Ovendal, A, Westblad, N, Ten Siethoff, L, Rosdahl, H, and Psilander, N. Effect of the intrasession exercise order of flywheel resistance and high-intensity interval training on maximal strength and power performance in elite team-sport athletes. J Strength Cond Res XX(X): 000–000, 2023—This study aimed to investigate the effect of intrasession exercise order of maximal effort flywheel resistance training (RT; 4 × 6 repetitions [rep]) and high-intensity interval training (HIIT, 2–4 × 8 rep of 20 secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
0
0
Order By: Relevance
“…High-intensity interval training is commonly used in elite team sports when training to increase V̇ o 2 max because it maximizes training time at a high intensity and is required for trained individuals to further develop aerobic capacity ( 16 ). We have previously demonstrated that very short and intense HIIT (3 set of 8 × 20 seconds of work, ∼8 minutes of total work [TW]) is a highly effective training protocol to increase V̇ o 2 max in elite team sport athletes ( 25 ). The downside with such HIIT is the degree of muscle tension, possibly increasing the level of neuromuscular fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…High-intensity interval training is commonly used in elite team sports when training to increase V̇ o 2 max because it maximizes training time at a high intensity and is required for trained individuals to further develop aerobic capacity ( 16 ). We have previously demonstrated that very short and intense HIIT (3 set of 8 × 20 seconds of work, ∼8 minutes of total work [TW]) is a highly effective training protocol to increase V̇ o 2 max in elite team sport athletes ( 25 ). The downside with such HIIT is the degree of muscle tension, possibly increasing the level of neuromuscular fatigue.…”
Section: Introductionmentioning
confidence: 99%